Exploring farmer perceptions of agricultural innovations for maize-legume intensification in the mid-hills region of Nepal - Victoria Alomia-Hinojosa; Erika N. Speelman; Arun Thapa; Hsiang-En Wei; Andrew J. McDonald; Pablo Tittonell; Jeroen C. J. Groot (International Journal of Agricultural Sustainability, 2018)
Maize-legume intercropping is a fundamental component of mixed farming systems in the mid-hills of Nepal. However, its productivity is constrained by several biophysical and social factors, and limited adoption of proven agricultural innovations. In this study, we assessed the productivity impact of a selection of relevant agricultural innovations and changes in the associated perceptions of farmers through a series of two-year participatory on-farm trials. The evaluated innovations resulted in higher yields as compared to farmers' current practices. The active involvement of farmers enlarged our understanding of underlying decision-making factors to adopt or non-adopt agricultural innovations. Additionally, the in-depth farmer engagement in our onfarm trials positively influenced farmer perceptions of the innovations and their interest to adopt the agricultural innovations. Yet, farmers final decisions to adopt some of the evaluated innovations were limited by a host of factors including labour scarcity, the availability of inputs, and by cultural preferences despite the increased yields. This was particularly true for low and medium resource-endowed farmers. This study shows the importance of active farmer participation and context-specific design of research and development projects aiming for local impact.